Blackwell companion to sociology / edited by - "Blau, Judith R.(ed.)" (Malden, 2004)
The Blackwell Companion to Sociology is a milestone collection of new essays by renowned sociologists, covering both the traditions and strengths of the field as well as newer developments and directions. Authors from the US, the UK, Europe and elsewhere have contributed to this all-in-one reference work, highlighting the relevance of interdisciplinary and international perspectives, while at the same time representing the scope and quality of sociology in its current form.
Keywords: Sociology